Cell surface binding, uptaking and anticancer activity of L-K6, a lysine/leucine-rich peptide, on human breast cancer MCF-7 cells - Che Wang (Nature Portfolio, 2017)
Abstract Cell surface binding and internalization are critical for the specific targeting and biofunctions of some cationic antimicrobial peptides (CAPs) with anticancer activities. However, the detailed cellular process for CAPs interacting with cancer cells and the exact molecular basis for their anticancer effects are still far from being fully understood. In the present study, we examined the cell surface binding, uptaking and anti-cancer activity of L-K6, a lysine/leucine-rich CAP, in human MCF-7 breast cancer cells. We found that L-K6 preferentially interact with MCF-7 cells. This tumor-targeting property of L-K6 might be partially due to its interactions with the surface exposed and negatively charged phosphatidylserine. Subsequently, L-K6 could internalize into MCF-7 cells mainly through a clathrin-independent macropinocytosis, without significant cell surface disruption. Finally, the internalized L-K6 induced a dramatic nuclear damage and MCF-7 cell death, without significant cytoskeleton disruption and mitochondrial impairment. This cytotoxicity of L-K6 against MCF-7 cancer cells could be further confirmed by using a mouse xenograft model. In summary, all these findings outlined the cellular process and cytotoxicity of L-K6 in MCF-7 cancer cells, and might help understand the complicated interactions between CAPs and cancer cells.